2019
DOI: 10.1186/s13068-019-1542-4
|View full text |Cite
|
Sign up to set email alerts
|

Drop-in biofuel production using fatty acid photodecarboxylase from Chlorella variabilis in the oleaginous yeast Yarrowia lipolytica

Abstract: Background Oleaginous yeasts are potent hosts for the renewable production of lipids and harbor great potential for derived products, such as biofuels. Several promising processes have been described that produce hydrocarbon drop-in biofuels based on fatty acid decarboxylation and fatty aldehyde decarbonylation. Unfortunately, besides fatty aldehyde toxicity and high reactivity, the most investigated enzyme, aldehyde-deformylating oxygenase, shows unfavorable catalytic properties which hindered hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…In addition, this enzyme requires the co-expression of ferredoxin to supply an electron transfer system. For bio-alkane production, upregulation and subsequent accumulation of fatty aldehyde precursors is problematic due to the reactive and toxic nature of these compounds [9,20,44,45]. In spite of this, multiple studies have demonstrated successful moderate production of gaseous and non-gaseous hydrocarbons in Escherichia coli and other microorganisms [5, 8-10, 20, 46].…”
Section: Deformylation: Aldehyde Deformylating Oxygenasementioning
confidence: 99%
“…In addition, this enzyme requires the co-expression of ferredoxin to supply an electron transfer system. For bio-alkane production, upregulation and subsequent accumulation of fatty aldehyde precursors is problematic due to the reactive and toxic nature of these compounds [9,20,44,45]. In spite of this, multiple studies have demonstrated successful moderate production of gaseous and non-gaseous hydrocarbons in Escherichia coli and other microorganisms [5, 8-10, 20, 46].…”
Section: Deformylation: Aldehyde Deformylating Oxygenasementioning
confidence: 99%
“…Detection of HCs was performed by gas chromatography as described by [14] Rate 20, final temp. 300 °C, hold 5 min.The analytical GC grade standards undecane, tridecane, pentadecane, heptadecane and the C8-C20 alkane standard solution were purchased at Sigma-Aldrich.…”
Section: Analysis Of Hcs With Gas Chromatography (Gc)mentioning
confidence: 99%
“…In order to transfer the genes required for carotenoid production, the prototrophic strains had to be made auxotrophic for uracil in order to enable application of the in yeast commonly applied URA3 marker gene for selection. Disruption of the native, chromosomal URA3 gene in all strains of this study was performed using a CRISPR-Cas9 system harboring a hygromycin marker cassette, [8] CRISPRyl-Hyg-URA3. Transformation, counterselection on 5-fluoroorotic acid and verification by sequencing are de-scribed in the above mentioned study.…”
Section: Strain and Plasmid Constructionmentioning
confidence: 99%
“…Yeast strains were cultivated in YPD medium and 180 rpm in Cellstar 24-well cell culture plates (Greiner bio-one, Austria) using a custom microwell plate-holder described in ref. [8]. For the determination of optical density, a PHERAstar FSX microplate reader (BMG Labtech, Germany) was used.…”
Section: Microwell Cultivation To Evaluate Different Temperature Condmentioning
confidence: 99%